Compatibilty Of Pseudomonas Fluorescens With Different Fungicides Used In Management Of Citrus Diseases (Journal of Plant Disease Sciences, 2022)
An experiment was conducted to study the compatibility of fungicides with bacterial biocontrol agents Pseudomonas fluorescens under in vitro conditions with five fungicides commonly used in management of Citrus diseases by employing poisoned food technique. Each fungicide was tested at diffrent concentrations from(Trace), 0.05%, 0.1%, 0.2%,0.3%, 0.4% and 0.5% in case of Bordeaux mixture upto 2.0%. For that purpose four Pseudomonas fluorescens isolates i.e. Pf 1, Pf2, Pf 7 and Pf 26 used. The results of the study proved that, Out of five fungicides, P. fluorescens showed good adaptation with Metalaxyl, Fosetyl-Al and Bordeaux mixture.
Keywords: Pseudomonas fluorescens; Fungicides; Citrus